EMPOWERMENT OF CATTLE FARMER GROUPS THROUGH THE DEVELOPMENT OF COMPOST ORGANIC FERTILIZER AND DIGITAL MARKETING TRAINING TO CREATE A HEALTHY AND PROSPEROUS ENVIRONMENT - Maulana, Hendri; Nurhayati, Immas; Marlina, Asti; Miranti, Miranti; Shalsabila, Mutiara (LPPM Univ. Ibn Khaldun Bogor, 2025)
The objective of this Community Empowerment Partnership (PKM) activity is to enhance the knowledge and skills of cattle farmer groups in Cilebut Barat Village, Sukaraja Subdistrict, Bogor Regency, in processing accumulated livestock manure waste and converting it into compost organic fertilizer (POK) with economic value, and marketing the product digitally. The programme of study was delivered through a combination of didactic methods, including lectures, video screenings, question-and-answer sessions, practical sessions, and simulations. As a result, farmers gained knowledge and skills in processing cow manure waste. After the training, they were able to produce POK as a new product and market it digitally. Thereafter, the training enabled the production of POK as a new product, which was subsequently marketed digitally.